A novel HSPB1 mutation associated with a late onset CMT2 phenotype: Case presentation and systematic review of the literature. Issue 3 (8th July 2020) - Taga, Arens; Cornblath, David R.
Abstract: Mutations in the HSPB1 gene are associated with Charcot‐Marie‐Tooth (CMT) disease type 2F (CMT2F) and distal hereditary motor neuropathy type 2 (dHMN2). More than 18 pathogenic mutations spanning across the whole HSPB1 gene have been reported. Three family members with a novel p.P57S (c.169C>T) HSPB1 mutation resulting in a late onset axonal neuropathy with heterogeneous clinical and electrophysiological features are detailed. We systematically reviewed published case reports and case series on HSPB1 mutations. While a genotype‐phenotype correlation was not obvious, we identified a common phenotype, which included adult onset, male predominance, motor more frequently than sensory involvement, distal and symmetric distribution with preferential involvement of plantar flexors, and a motor and axonal electrophysiological picture.